Does Navigation Always Predict Performance? Effects of Navigation on Digital Reading are Moderated by Comprehension Skills - Naumann, Johannes; Salmerón, Ladislao (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
This study investigated interactive effects of navigation and offline comprehension skill on digital reading performance. As indicators of navigation relevant page selection and irrelevant page selection were considered. In 533 Spanish high school students aged 11-17 positive effects of offline comprehension skill and relevant page selection on digital reading performance were found, while irrelevant page selection had a negative effect. In addition, an interaction between relevant page selection and offline comprehension skill was found. While the effect of relevant page selection was strong in good offline comprehenders, it was significantly reduced in weak offline comprehenders. The effect of offline comprehension skill was strong in students showing high rates of relevant page selection, while it was weak and insignificant in students showing low rates of relevant page selection.